2019
DOI: 10.3390/pathogens8020057
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Robigovirus Species from Sweet Cherry in Turkey

Abstract: High throughput sequencing of total RNA isolated from symptomatic leaves of a sweet cherry tree (Prunus avium cv. 0900 Ziraat) from Turkey identified a new member of the genus Robigovirus designated cherry virus Turkey (CVTR). The presence of the virus was confirmed by electron microscopy and overlapping RT-PCR for sequencing its whole-genome. The virus has a ssRNA genome of 8464 nucleotides which encodes five open reading frames (ORFs) and comprises two non-coding regions, 5′ UTR and 3′ UTR of 97 and 296 nt, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The percentage identities of RdRp and CP nucleic acid and the translated amino acid sequences confirmed that both contigs are independent full genomes of BanMMV [ 33 ].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The percentage identities of RdRp and CP nucleic acid and the translated amino acid sequences confirmed that both contigs are independent full genomes of BanMMV [ 33 ].…”
Section: Resultsmentioning
confidence: 90%
“…The particles were approximately 580 nm in size, suggestive of members of the family Betaflexiviridae. Like all virions of the latter family, these particles showed a diameter ranging from 10 to 15 nm [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the assembled contigs, two primer pairs amplifying partial sequences of the NIa-Pro (6564F: 5 -TTT GGT TTT CGT CAC TGG AT-3 /7030R: 5 -GTG ACT GGT GTG AAG TAG TT-3 ) and of the coat protein (CP) regions (8985F: 5 -CTGGATGTGATTGAGTTACC-3'/9753R: 5 -CAAGAGGTTTTCATGCCAG-3 ) were designed to confirm the HTS-assembled sequences and fulfillment of the survey. Reaction ingredients, conditions, and thermal cycling for RT-PCR were as described previously [21]. The amplified fragments were cleaned up using PCR purification kit (Qiagen) and directly sequenced in both directions by Medsantek (Istanbul, Turkey).…”
Section: Virus Detection By Rt-pcrmentioning
confidence: 99%
“…The subfamily Quinvirinae contains three genera – Carlavirus , Foveavirus and, Robigovirus – and three floating species, including Banana mild mosaic virus (recently proposed genus “Banmivirus”), Banana virus X , and Sugarcane striate mosaic associated virus (proposed genus “Sustrivirus”; Candresse et al, 2021 ). Quinviruses have a plus-sense RNA genome (5.8–9.0 kb; 5' capped and 3' polyadenylated ends) with six open reading frames (ORFs) for carlaviruses or five ORFs for the other two genera and floating species, with some exceptions ( Caglayan et al, 2019 ; Zheng et al, 2020 ). Members of the Quinvirinae encode the so-called triple-gene block (TGB) for cell-to-cell movement in the leaf epidermis, and are clearly differentiated from the members of the subfamily Trivirinae , whose genomes encode a single movement protein (the 30K superfamily).…”
Section: Introductionmentioning
confidence: 99%